Encouraging lifelong learning through student-centred learning approaches in a Malaysian teacher education programme - Tengku Kasim, Tengku Sarina Aini; Furbish, Dale (2010)
Student-centred learning approaches employ activities that are intended to assist students to construct their own understandings and develop skills relevant to problem solving. These approaches are intended to promote development of learning skills, knowledge, attitudes and competencies for lifelong learning. In the student-centred environments, teachers relinquish being the main actor in the classroom for a facilitator‟s role. Students become active agents in the classroom where they learn how to assimilate and accommodate new information and to build new knowledge based on existing knowledge. This paper examines student-centred learning models as an alternative to traditional teacher-centred learning models. The report will present preliminary results of a case study that investigated the use of student-centred approaches at a Malaysian university teacher education programme. The qualitative approach examined teaching and learning from both the lecturers‟ and students‟ points of view. The results supported the notion of studentcentred learning in educating students toward the direction of lifelong learning development. The infusion of student-centred learning into courses in the teacher education programme provides students with opportunities to gain skills and knowledge needed to become teachers who contribute to a more lifelong learning in their classrooms. There is evidence from the study that studentcentred learning can nurture the students towards greater intrinsic motivated, self-expression and independence in their learning patterns and hence develop their lifelong learning process.